2015
DOI: 10.5539/elt.v8n10p60
|View full text |Cite
|
Sign up to set email alerts
|

The Repetition of Chunks in Korean Middle School English Textbooks

Abstract: The current study aims to examine the use of chunks and the extent of repetition in Korean middle school English textbooks. Also, the number of chunks shared by three publishers is examined. To create the corpora, 9 textbooks from three publishers were filed and processed by Simple Concordance Program. The results showed that chunk expressions were repeated 3.6 times on average. Most collocations occurred only one to two times throughout the same series of textbooks. Fixed-expressions showed similar results to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Thus, teaching materials for EFL learners also need to be assessed on the repetition and frequency they give to individual collocation types. Results of previous research, however, vary in such assessments; some researchers observed that textbooks tend to provide a limited amount of collocation repetition (Tsai, 2015;Lee, 2015), while others report the opposite trend (Shin, 2019).…”
Section: Assessment Of Collocation In Elt Materialsmentioning
confidence: 97%
See 2 more Smart Citations
“…Thus, teaching materials for EFL learners also need to be assessed on the repetition and frequency they give to individual collocation types. Results of previous research, however, vary in such assessments; some researchers observed that textbooks tend to provide a limited amount of collocation repetition (Tsai, 2015;Lee, 2015), while others report the opposite trend (Shin, 2019).…”
Section: Assessment Of Collocation In Elt Materialsmentioning
confidence: 97%
“…Unlike the curriculum wordlist, which has been continuously revised to improve its representativeness based on highly objective criteria, such as word frequency, range, and teacher ratings for item familiarity (Lee & Shin, 2015), only marginal attention has been paid towards the development of a curriculum-related, statistically verified collocation list exploiting a large-scale reference corpus data. A few researchers (Lee, 2009(Lee, , 2015Shin, 2019) have thus called for the need to establish curriculum guidelines and objective criteria to select pedagogically meaningful collocations. Research has also pointed out the restricted collocation repertoire in textbooks, for example, limited in their diversity of Part of Speech (POS) types (Kim, 2004;Shin, 2019), complexity (Shin, 2019), or the level of repetition (Lee, 2015;Tsai, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A few studies have investigated collocational profiles and the recycling of targeted collocations in EFL textbooks (Lee, 2015;Tsai, 2015;Wang & Good, 2007). In a study examining a three English textbook series used in Korean middle schools, Lee (2015) found that verb-noun collocations were used twice in the whole series.…”
Section: Collocations In Textbooksmentioning
confidence: 99%
“…A few studies have investigated collocational profiles and the recycling of targeted collocations in EFL textbooks (Lee, 2015;Tsai, 2015;Wang & Good, 2007). In a study examining a three English textbook series used in Korean middle schools, Lee (2015) found that verb-noun collocations were used twice in the whole series. Wang and Good (2007) tabulated verb-noun collocations in Taiwanese high school textbooks and found that 80% of collocations was repeated only 1 to 5 times through the whole series of textbooks.…”
Section: Collocations In Textbooksmentioning
confidence: 99%